O3.6. PREVALENCE OF AND RECOVERY FROM COMMON MENTAL DISORDERS INCLUDING PSYCHOTIC EXPERIENCES. (18th May 2020) - Perez, Jesus; Knight, Clare; Russo, Debra A; Stochl, Jan; Jones, Peter B
Abstract: Background: Systematic reviews indicate that approximately one third of people with at-risk mental states for psychosis (ARMS) will transition to a psychotic disorder. Research in non-specialised services, such as primary care settings, has shown that far fewer make such a conversion. Nonetheless, psychotic experiences (PE) may also be linked to common mental disorders (CMD), particularly depression and anxiety, and still predict poor outcomes. Population studies modelling the co-occurrence of CMD and PE have found an underlying unitary psychopathological factor, with PE emerging towards its more severe end. We know little about the prevalence of and recovery from PE in primary mental health care, where most CMD are treated. One example of primary mental health care setting in England is the Improving Access to Psychological Therapies (IAPT) programme (https://www.england.nhs.uk/mental-health/adults/iapt/ ). The IAPT programme provides evidence-based psychological therapies for mild to moderate CMD across the UK National Health Service (NHS). IAPT services adhere to current diagnostic paradigms and, therefore, do not either measure or treat PE. We aimed to establish the prevalence of PE in a large sample of patients with CMD from the IAPT programme and compare recovery rates between patients with CMD and PE (CMD-P) and those without PE. Methods: We used the Community Assessment of Psychic Experiences - Positive 15-item Scale (CAPE-P15) to determine the prevalence of PE in patients with CMD receiving treatment from IAPT services across England. We employed the CAPE-P15 threshold score of 1.47, which identifies individuals with ARMS, and also a lower threshold of 1.30, chosen as within one standard error of measurement, in order to explore threshold effects in the association between PE and recovery. Patient-reported measures of depression (PHQ-9) and anxiety (GAD-7) are routinely collected in IAPT services and determine 'caseness' before, during and after therapy. Using recovery rates (moving from 'caseness' to recovery) monitored nationally in the IAPT programme, we stratified patients according to the absence and presence of PE. Multi-group growth models estimated improvement trajectories for each group. Results: 2, 042 patients with CMD completed the CAPE-P15. The mean age was 39.8. The overall prevalence of CMD-P was 29.68% at CAPE-P15 threshold score for ARMS, i.e. 1.47, and 48.09% at threshold score 1.30. The overall recovery rate at threshold of 1.47 was 27.87% and 36.3% at 1.30. Recovery rates for those without PE were 58.92% and 62.43% for thresholds 1.47 and 1.30, respectively. Although patients with or without PE shared similar improvement trajectories, the initial severity of patients with CMD-P impeded their likelihood of recovery during treatment. Discussion: At least one in four patients receiving treatment from IAPT services in primary care experience CMD-P. This significant group of people experience a lower recovery rate, with adverse implications not only for them but also for efficiency of services. Although recovery trajectories for this group showed improvement over therapy sessions, remittance of symptoms was insufficient to meet national IAPT standards of recovery. This patient group is not well-served by current interventions in primary care. This work forms part of a nation-wide NIHR research programme (TYPPEX; https://www.nihr.ac.uk/news/innovative-mental-health-study-launchesin-eastern-region ) aiming to develop innovative therapies for people with CMD-P in primary care. Preliminary results related to feasibility and effectiveness of new therapeutic approaches will also be presented.